Sozialistische Großfamilie - Zajas, Paweł (De Gruyter, 2024)
The article offers an analysis of transnational contacts as they developed in the GDR through cultural exchange within the Eastern Bloc and the international cultural policies of the socialist states. First, the archives of the German Writers Union are used to show how, paradoxically, the processes of transnational coopera- tion that began after 1956 led to a policy of isolation of the GDR. Secondly, it is de- monstrated that the cultural exchange between the GDR and the socialist partners began to recover relatively quickly from the “Kahlschlag Plenum”, which took place in the late 1960 s, and that the rapidly developing interdependencies also resulted in certain innovations in the GDR’s literary scene. Finally, it is shown how the publi- shing cooperation between socialist publishers, which has intensified since the mid- 1970s (through joint multilateral edition projects, transfer of translated literature) may be interpreted as a direct consequence of the Helsinki Final Act (1975).
Die DDR und literarisch-verlegerische Verflechtungen im europäischen Ostblock
Keywords: socialist transnationalism; East-European literature; sociology of literature; sociology of translation; socjalistyczny transnacjonalizm; wschodnioeuropejskie pole literackie; socjologia literatury; socjologia przekładu; literatura światowa; world literature